Affirmative Jury Selection: A Proposal to Advance Both the Deliberative Ideal and Jury Diversity The Right to a Fair Trial - Ramirez, Deborah (University of Chicago Legal Forum, 1998)
Disclaimer: This summary was generated by AI based on the content of the source document.